Impact of clinical and dosimetric factors on severe oral mucositis in head and neck cancer: insights from a phase II clinical trial - Lozano-Borbalas, Alicia; Jordi-Ollero, Olivia; Marruecos, Jordi; Farre, Nuria; Planas, Isabel; Toledo, Maria Dolores; Mesia, Ricard; Navarro-Martin, Arturo (Frontiers in Oncology, 2025)
IntroductionOral mucositis (OM) is the most common acute treatment-limiting adverse effect in patients with head and neck cancer (HNC), particularly following concomitant radiotherapy (RT) and systemic therapy. However, the effects of clinical and dosimetric parameters on the onset of severe OM remain controversial. We aimed to determine the association between clinical and dosimetric parameters and severe OM in the oral and pharyngeal mucosae in a randomized phase II clinical trial.Patients and methodsA subgroup analysis of data from a clinical trial was conducted to assess the efficacy of a 3% melatonin oral gel (MucomelR) to prevent OM in patients with HNC. A total of 54 patients treated with intensity-modulated radiotherapy (IMRT) (66–69.96 Gy/33 fractions) plus concomitant systemic therapy (cisplatin or cetuximab) +/− melatonin rinses were included. The association between clinical and dosimetric parameters and grade (G) ≥3 OM was determined. For this analysis, the oral mucosa was divided into the oral and pharyngeal mucosae.ResultsThe following variables were significantly associated with G3 OM in the oral mucosa: oropharyngeal localization (p = 0.03), treatment with cetuximab (p = 0.01), oral mucosa volume included in low planning target volume (PTV) (PTV1: 54.12 Gy) and intermediate treatment doses (PTV2: 60 Gy), V35 >70% (p = 0.007), and a median RT dose of 56.6 Gy (p = 0.02). The absolute healthy volume of the oral mucosa was a significant protective factor (p = 0.03; McFadden’s pseudo-R2 = 0.46). None of the clinical or dosimetric variables was significantly associated with G3 OM in the pharyngeal mucosa.ConclusionOropharyngeal cancer, cetuximab, and low and intermediate RT dose to the oral cavity mucosa were significantly associated with the onset of severe oral mucositis. Given the association between these previous factors with a higher risk of G3 OM, they should be considered during treatment planning and dosimetry in patients treated with cetuximab for oropharyngeal cancer.